Estudos químicos e biológicos de compostos heterocíclicos derivados dos núcleos imidazolidina-2,4-diona e 2-tioxoimidazolidina-4-ona - Souza, Severino Araújo de (2015)
The breakthrough occurred in the scientific world involving chemical and pharmacological studies of heterocyclic are the result of the large investment from pharmaceutical companies and research centers in universities. Synthetic Heterocyclic compounds stand out because of the possibilities these compounds present several different biological properties. Structural changes in imidazolidínico and tioimidazolidínico rings can change their chemical, physical properties and produce biological effects with a variety of useful applications. The objective of this work was the synthesis and characterization of heterocyclic compounds of imidazolidine-2,4-dione class and 2-thioxo-imidazolidine-4-one in order to investigate their pharmacological potential as antimicrobial, antinociceptive, anti-tumor and anticonvulsant and study their thermal stability. The compounds were obtained in two steps: first, reacted sodium cyanide, ammonium chloride, methylammonium chloride, isopropylammonium chloride and substituted aromatic aldehydes to, followed by acid hydrolysis to form the amino acid derivatives of glycine. In the second stage, there was the reaction of amino acids prepared with potassium isocyanate and ammonium isothiocyanate and / or phenyl isocyanate and / or phenyl isothiocyanate followed by acid hydrolysis to form the imidazolidínicos derivatives: IM-15; HPA-05; HPA-09; HPA-10; HPA-14; HPA-15A; HPA-15B; HPA-15C; HPA-15D; HPA-15E; HPA-15F; HPA-15G; HPA-15H; HPA-15J and tioimidazolidínicos: HPA-03; HPA-04; HPA-08; HPA-11; HPA-15I; HPA-15M. The structures of the synthesized compounds were characterized by IR absorption spectroscopy, 1H-NMR and 13C-NMR. With the synthesized compounds investigated the potential front Antimicrobial studies, antinociceptive, anticarcinogenic and CNS. Also evaluated the thermal stability of the synthesized compounds and in silico studies.